Claisen Rearrangement Toward Cyclic Compound on Different Organic Synthesis Methods: Short Review - Saputra, Rizki Rachmad; Rosalina, Reny; Pramudita, Dimas; Wulandari, Oktavia Rahmi; Yuneta, Yuneta; Gracia, Amanda Natania; Sugiyani, Tina; Imelya, Marsya (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2023)
The synthesis of functional and complex organic compounds is majorly performed by the Claisen rearrangement method. Claisen rearrangement is one of [3,3] sigmatropic rearrangements, a complex method in the synthesis of organic compounds, where it is mostly used to construct stereoselective compounds. It can be combined with other synthesis methods to synthesize organic compounds giving satisfactory results based on the method used, temperature, time, and yield produced. This review aimed to summarize several recent advances in synthesizing organic compounds through Claisen rearrangement reactions. An understanding of the mechanism and applications of this reaction might improve the ability to synthesize innovative and useful organic compounds in various fields of life sciences.